2001
DOI: 10.1146/annurev.neuro.24.1.1071
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Dendritic Spines Associated with Long-Term Synaptic Plasticity

Abstract: Dendritic spines are morphological specializations that receive synaptic inputs and compartmentalize calcium. In spite of a long history of research, the specific function of spines is still not well understood. Here we review the current status of the relation between morphological changes in spines and synaptic plasticity. Since Cajal and Tanzi proposed that changes in the structure of the brain might occur as a consequence of experience, the search for the morphological correlates of learning has constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
820
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,136 publications
(863 citation statements)
references
References 85 publications
26
820
0
6
Order By: Relevance
“…The function of dendritic spines has been extensively investigated (Shepherd, 1996;Yuste and Bonhoeffer, 2001;Sabatini et al, 2001;Nimchinsky et al, 2002). Regarding their individual geometrical dimensions, recent studies have proposed that spine length in hippocampal pyramidal neurons contributes to spine-dendrite coupling of Ca 2+ signals Korkotian et al, 2004;Majewska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of dendritic spines has been extensively investigated (Shepherd, 1996;Yuste and Bonhoeffer, 2001;Sabatini et al, 2001;Nimchinsky et al, 2002). Regarding their individual geometrical dimensions, recent studies have proposed that spine length in hippocampal pyramidal neurons contributes to spine-dendrite coupling of Ca 2+ signals Korkotian et al, 2004;Majewska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that long and thin spines may isolate synaptically initiated spine Ca 2+ transients from the parent dendrite and neighboring spines , and that synchronously coordinated dendritic and spine Ca 2+ transients are critical for synaptic plasticity (Yuste and Bonhoeffer, 2001;Sabatini et al, 2001), BDNF may enhance synaptic plasticity not only by increasing spine density, but also the proportion of Type-I stubby spines. These larger spines with wider necks are thought to represent spines that acquired AMPA receptors immediately after the induction of long-term potentiation (Matsuzaki et al, 2001;Kasai et al, 2003), and thus enhance spine-dendrite coupling leading to widespread dendritic Ca 2+ signaling during excitatory synaptic transmission (Noguchi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, recent studies by Govek et al showed that knock-down of OPHN1 expression in CA1 pyramidal neurons in hippocampal slices results in a significant decrease in dendritic spine length [30]. As spine morphology is ultimately linked to synaptic function [89], such spine morphological changes are likely to compromise synaptic plasticity, and potentially lead to learning and memory deficits. The above spine length phenotype was mimicked using a constitutive active RhoA (CA-RhoA) mutant and could be largely rescued by inhibiting the RhoA effector, Rho-kinase (Govek et al 2004).…”
Section: Oligophrenin-1mentioning
confidence: 99%
“…These dynamic changes are determined by the architecture of its actin cytoskeleton [94]. Significantly, increasing evidence indicates that proper regulation of spine shape and size is crucial for processing of information [13,44,52,55,89]. For instance, spine morphology and/or dynamics have been associated with long-term potentiation (LTP) and long term-depression (LTD), which are two well studied forms of learning and memory [55].…”
Section: Introductionmentioning
confidence: 99%
“…We prefer the original Lynch and Baudry proposal that changes in receptor number are secondary to changes in the size of the synaptic zone (the post synaptic density, psd), which themselves are secondary to alterations in spine morphology. The original impetus for this idea came from ultrastructural studies showing that shifts in spine and psd morphology accompany LTP (Lee et al, 1980), an observation subsequently greatly expanded by analyses with electron microscopic (Yuste and Bonhoeffer, 2001 for review) and newly developed light microscopic Lin et al, 2005) methods.…”
Section: Expressionmentioning
confidence: 99%